Evaluación de un Biofertilizante a base de Bacillus subtilis + Pseudomonas fluorescens en dos variedades mejoradas de cebada (Hordeum Vulgare L.), en dos épocas de aplicación y con el uso de materia orgánica, bajo invernadero en la EESC. - Pastuña Pilaguano, Oscar Washington (2023)
The study was carried out at the Cereal Program in the Santa Catalina Experimental Station of the National Institute of Agricultural Research (INIAP) in the Cutuglagua parish, Mejía Canton, Pichincha Province, Ecuador. The general objective was to evaluate a biofertilizer based on Bacillus subtilis + Pseudomonas fluorescens in two improved varieties of barley (Hordeum vulgare L.), in two application seasons and with the use of organic matter, under greenhouse. For which activities were carried out that allowed to evaluate the response of Bacillus subtilis + Pseudomonas fluorescens in the two varieties of barley INIAP-Cañicapa 2003 and INIAP-Alfa 2021, identify the concentration of application of Bacillus subtilis + Pseudomonas fluorescens in the barley crop, establish the application times of Bacillus subtilis + Pseudomonas fluorescens during its development, determine the response of Bacillus subtilis + Pseudomonas fluorescens in soils with two levels of organic matter and determine the best treatment in response to Bacillus subtilis + Pseudomonas fluorescens of the barley varieties. Completely Random Block Design (DBCA) with a factorial arrangement of A×B×C×D + 4N (additional/ witnesses) was stablished, resulting in 28 treatments total, in 4 repetitions. For the data analyses was made the Kolmogorov and Kruskal Wallis tests, generating ANOVAS, media tables and figures for the evaluated variables: days to heading, plant height, amount of green and dry matter, length of spike, number of grains per spike, grain weight and yield based on the Manual No. 111 Evaluation and Selection Parameters in Cereals and for the count of colony-forming units (CFU) according to Manual No. 112 on Quality Analysis for Formulations Based on Fungi with Biocontrollers. With the data obtained was determined that the biofertilizer had a better effect on the variety INIAP-Alfa 2021 with the application of contraction 1×1011 CFU, while for the INIAP-Cañicapa 2003 variety the effective concentration is 1×1012 CFU, for both varieties the applications were determined in Zadocks 0 (inoculation) and in Zadocks 50 (heading) using organic matter, where the best result is the V2C2E2M2 treatment with a productive potential of 5728.8 kg ha-1 under greenhouse.